Hypersensitive response of beans to Apion Godmani (Coleoptera: Curculionidae) - Garza García, Ramón; Vera, J.; Cardona Mejía, César; Barcenas Ortega, NM; Singh, Shree P. (2001)
High levels of resistance to Apion godinani Wagner have been reported in bean, Phaseolus vulgaris L., landraces from Mexico. We report on the role of hypersensitivity to A. godmani in five resistant and three susceptible bean genotypes. In susceptible genotypes (cultivars 'Canario 107','Jamapa', and 'Zacatecas 45'), the eggs and first instars of A. godmani were embedded in the pod mesocarp and usually were surrounded by healthy tissue. In contrast, in resistant landraces ('Amarillo 154', 'Amarillo 155', 'J-117', 'Puebla 36', and 'Pinto 168'), necrotic tissues developed concentrically around the oviposition site, encapsulating eggs and dead larvae. An inverse relationship between percentage egg and larval encapsulation at the early immature pod stages and percentage of damaged seeds at harvest was found. Results indicate that hypersensitivity in developing pods plays an important role in antibiosis to A. godmani in beans. This information will facilitate future genetic and biochemical research and provide much needed information concerning the phenotypic basis of resistance to A. godmani in bean.